2006
DOI: 10.1021/jp063972n
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Solar Cells Based on Anatase TiO2 Nanoparticle/Nanowire Composites

Abstract: Dye-sensitized solar cells were fabricated based on the composites of anatase TiO2 nanoparticles and single crystalline anatase TiO2 nanowires. Nanoparticle/nanowire composites can possess the advantages of both building blocks, i.e., the high surface area of nanoparticle aggregates and the rapid electron transport rate and the light scattering effect of single-crystalline nanowires. Three different composites were prepared with 5 wt %, 20 wt %, and 77 wt % nanowires, respectively. The performances of composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
378
4
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(397 citation statements)
references
References 37 publications
(55 reference statements)
10
378
4
5
Order By: Relevance
“…For the TiO 2 system, a 20% (by weight) NW content increased the PCE to 8.6% from 6.7% for the pure NP-DSSC [38]. For the ZnO system, the mixed NP-NW mercurochrome-sensitized DSSC saw an improvement of PCE from 0.45% (pure NP) to 2.77% (V oc = 0.58 V, J sc = 8.33 mA cm -2 , FF = 0.58) using 5.5 μm-long NWs [39].…”
Section: Photovoltaicsmentioning
confidence: 97%
“…For the TiO 2 system, a 20% (by weight) NW content increased the PCE to 8.6% from 6.7% for the pure NP-DSSC [38]. For the ZnO system, the mixed NP-NW mercurochrome-sensitized DSSC saw an improvement of PCE from 0.45% (pure NP) to 2.77% (V oc = 0.58 V, J sc = 8.33 mA cm -2 , FF = 0.58) using 5.5 μm-long NWs [39].…”
Section: Photovoltaicsmentioning
confidence: 97%
“…More insight about the stability and bonding nature of these nanowires can be provided by examining three isomers of B4 structure. B4a is uniform B4 in which d 2-4 = d [4][5] . Next isomer is shaped by forming Ti-Ti dimers, so B4 nanowire gains very small energy ͑about 10 meV͒ with respect to the B4a structure.…”
Section: A (Tio) N Nanowiresmentioning
confidence: 99%
“…In recent years, one-dimensional ͑1D͒ TiO x nanostructures 3 such as nanorods, nanowires, and nanotubes have been investigated extensively because of their size and morphology dependent structural, chemical and electronic properties. They lead to a significant number of technological applications including gas and humidity sensors, 4 dye-sensitized solar cells, 5,6 photovoltaics, and photocatalysis. 7 TiO 2 nanowires [8][9][10][11][12][13] can be synthesized on TiO 2 surfaces or in zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various types of nanostructured TiO2 such as nanoparticles, nanotubes, nanowires, and nanorods have been prepared and adopted as electrode materials to improve the performances of DSSCs [21][22][23][24][25]. Tan et al [26] synthesized TiO2 nanoparticles attached to TiO2 nanowires to increase the surface area and applied them as a DSSC electrode material. They reported that the resulting DSSC had a powerconversion efficiency of 8.6%, which is 2% higher than the efficiency of the cell with a TiO2 nanoparticle electrode.…”
Section: Introductionmentioning
confidence: 99%